Witches In Space: Introduction - O'Malley, Sarah (Early Theatre, 2023)
The introduction to this Issues in Review entitled ‘Witches in Space’ sets out the critical history that forms the background work on the literary geographies of early modern witchcraft. The introduction first establishes the need for such work through an illustrative case study and then attends to the foundation of scholarship in the fields of literary and cultural geography as well as witchcraft studies on which this collection of essays builds.